Fine-scale foraging ecology of leatherback turtles - Wallace, Bryan P.; Zolkewitz, Michael; James, Michael C. (Frontiers in Ecology and Evolution, 2015)
Remote tracking of migratory species and statistical modeling of behaviors have enabled identification of areas that are of high ecological value to these widely distributed taxa. However, direct observations at fine spatio-temporal scales are often needed to correctly interpret behaviors. In this study, we combined GPS-derived locations and archival dive records (1 sec sampling rate) with animal-borne video footage from foraging leatherback turtles (Dermochelys coriacea) in Nova Scotia, Canada (Northwest Atlantic Ocean) to generate the most highly detailed description of natural leatherback behavior presented to date. Turtles traveled shorter distances at slower rates and increased diving rates in areas of high prey abundance, which resulted in higher prey capture rates. Increased foraging effort (e.g., dive rate, dive duration, prey handling time, number of bites) was not associated with increased time at the surface breathing to replenish oxygen stores. Instead, leatherbacks generally performed short, shallow dives in the photic zone to or above the thermocline, where they disproportionately captured prey at bottoms of dives and during ascents. This foraging strategy supports visual prey detection, allows leatherbacks to exploit physically structured prey at relatively shallow depths (typically <30m), and increases time turtles spend in warmer water temperatures, thus optimizing net energy acquisition. Our results demonstrate that leatherbacks appear to be continuously foraging during daylight hours while in continental shelf waters of Nova Scotia, and that leatherback foraging behavior is driven by prey availability, not by whether or not a turtle is in a resource patch characterized by a particular size or prey density. Our study demonstrates the fundamental importance of obtaining field-based, direct observations of true behaviors at fine spatial and temporal scales to enhance our efforts to both study and manage migratory species.